SITUASI MALARIA DI KOTA LUBUKLINGGAU PROVINSI SUMATERA SELATAN DALAM MENCAPAI ELIMINASI MALARIA TAHUN 2021 - Nungki Hapsari Suryaningtyas; Maya Arisanti (Balai Penelitian dan Pengembangan Kesehatan Baturaja, 2021)
Malaria is a vector borne disease and is one of the leading causes of mortality and morbidity worldwide. In general, the prevalence of malaria parasites differed between age and sex with the highest prevalence occurring in children and women. This study uses secondary data from the Lubuklinggau City Health Office in 2015 - 2018. The number of malaria cases in Lubuklinggau City has decreased during 2015 - 2018. Most cases of malaria occur in women. The distribution of malaria cases was highest in the age group 15 - 64 years and there were still cases in children aged 0 - 5 years. The most common type of Plasmodium found is Plasmodium vivax. To maintain malaria elimination, Lubuklinggau City must eliminate indigenous cases and improve treatment management and management of malaria cases.